Media Policy and Globalization - Paula Chakravartty, Katharine Sarikakis (Edinburgh University Press, 2006)
This book explores the conditions and ideas behind global communications policies; our writing travels back and forth, across continents and socioeconomic realities to identify and analyze common policy concerns, conflicting interests, and the place and voice of publics. Throughout the writing process, we relied heavily on electronic communications to update information, track down electronic archives and conduct basic literature searches. We conceived and discussed the ideas in this book first online and then by telephone and continued developing the book in the same way, with only one brief off-line meeting. We have used six different computers between us (two of which crashed) and have been dependent on Internet access with speedy connections (broadband). These tools were available to us as researchers based in academic institutions, in our homes and hotels and Internet cafes located in the connected parts of the world where we wrote this book – Amherst, Athens, Coventry, Kolkata, London, Montreal, Pittsburgh and Salvador – enabling us to communicate with colleagues across the world instantly. Access to technology and skills are important material and cultural capital not fairly we wrote. We recognize our privileged position as observers and critics and hope that we have been responsible in our use of these means to bring attention to some of the most urgent questions surrounding global communications and media policy.